Student Competence in Carrying Out Learning Evaluations in the Era of Independent Learning - Ramadhan, Muhammad Qadri; Inayati, Nurul Latifatul (CV Global Research Publication, 2024)
This era, introduced by the Minister of Education and Culture, Nadiem Makariem, emphasizes the freedom of teachers and students to innovate, learn independently, and be creative. Student competency in learning evaluation is considered crucial to ensure the successful implementation of this new educational program. The research method used is a literature study focusing on scientific work relevant to the concept of Independent Learning, learning evaluation, and the role of students in the evaluation process. The analysis is carried out to detail key concepts, compare the views of various researchers, and synthesize information to provide a holistic picture. The research results show that student competencies include understanding various evaluation methods, planning skills, active participation, data analysis, and effective communication about evaluation results. Students need to be able to face a holistic evaluation approach that covers various aspects, including cognitive, affective, and psychomotor. The research conclusion underlines the importance of developing student competencies in learning evaluation in the Merdeka Belajar era. Research suggestions include the need for support from schools, teachers, and parents and the need to hold training and workshops to improve students' skills. Collaboration between education stakeholders is essential to ensure that the evaluation approach implemented is appropriate to student needs and supports the achievement of national education goals.